Challenges in defining and measuring legibility, under Information Design perspective - Martins, Ricardo (InfoDesign, 2008)
The concept of legibility is surrounded by confusion and ambiguity. This creates all sorts of problems, including gaps in the interpretation of Brazilian law, concerning medical prescriptions. The law says it is forbidden to write illegible prescriptions. But even among scholars there is no consensus on what is "legible". The definition of this term is still controversial and uses subjective words like "easy", "different" and "familiar", obscuring its meaning. But the definition of legibility is not the only one that suffers from inconsistency. Many studies that tried to measure it from an objective perspective also has provoked debate since they lack ecological validity, that is, their results do not apply in real conditions of reading. Therefore, the word "legible", used in health legislation, is not clear enough to avoid confusion and doesn´t help doctors to assess if their prescriptions fall within the expected, keeping patients safe.